Adobe Illustrator CC Classroom in a book, 2018 release : the official training workbook from Adobe - Wood, Brian (Adobe instructor) (Classroom in a book., 2018)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe Illustrator CC (2018 release) choose Adobe Illustrator CC Classroom in a Book (2018 release) from the best-selling series of hands-on software training workbooks from Adobe Press. The 15 project-based lessons show users the key techniques for realizing your creative potential with Adobe Illustrator CC. Following hands-on step-by-step projects, users create logos, illustrations, posters, and more. Explore the new Essentials workspace that makes learning Illustrator even easier. Learn how to use the Shaper tool and Live Shapes along with dynamic symbols to streamline graphics creation. Create website assets and export them in multiple formats to support modern responsive web designs. From exacting illustration to free-form painting, you'll build a strong foundation in Illustrator as you progress through the lessons. The online companion files include all the necessary assets for readers to complete the projects featured in each chapter as well as ebook updates when Adobe releases relevant new features for Creative Cloud customers. All buyers of the book get full access to the Web Edition: a Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.